Optimization of the second phase morphology and content effect to impact resistance of epoxy resin composite - Fitri Muhamad; Mahzan Shahruddin; Muhammad Zago Dagaci; Zakaria Supa’at; Feriyanto Dafit (BIO Web of Conferences)
The increasingly widespread use of composite materials for structural materials forces composite materials to have superior mechanical properties, one of which is impact strength. The material’s impact strength was determined by calculating the impact energy obtained from the impact test. Many things impact the strength of composite materials. Many studies have been conducted on the mechanical properties of composite materials. However, the above research has not investigated the influence of the morphology of the second phase on the mechanical properties of resin composite materials. The morphology of the second phase used as reinforcement in composite materials can be particles, short fibers, or continuous fibers. The shape (morphology) of the second phase affects the impact strength of the composite material. Therefore, this study was intended to examine the effect of the morphology of Coir Coconut fiber as the second phase (reinforcement) combined with the percentage of its content in epoxy resin matrix composite on the impact strength, as well as to determine the optimum morphology and the percentage of the second phase. The study was designed using the full factorial. Furthermore, the data on the impact strength of the specimens were analyzed to obtain a regression model for the relationship between the morphology of the second phase and the percentage of the content of the second phase on the impact strength. With this regression model, it is possible to predict the impact strength of various morphological forms of the second phase and optimize the optimum content of the second phase.